2021
DOI: 10.1097/mou.0000000000000967
|View full text |Cite
|
Sign up to set email alerts
|

Thulium fiber laser in urology: physics made simple

Abstract: Purpose of reviewIn this narrative review, we will focus on a novel thulium fiber laser's physical properties in terms of its clinical applicability.Recent findings TFL has successfully moved forward from the preclinical trials into clinical practice and now is being widely used in clinics around the world. The available data suggest that the device effectively operates in soft tissues -benign prostate hyperplasia (BPH) and bladder tumors, as well as in lithotripsy. Also, the first promising results were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…As for QCW TFL, it has established itself as a effective and safe device for EEP which is not inferior in these terms to Tm : YAG and Ho : YAG. QCW TFL may be safer than Tm : YAG in terms of carbonizationthe quasi-continuous mode decreases the thermal damage to tissue reducing carbonization and simplifying the intraoperative navigation (16,17). Unfortunately, there is no one preclinical comparison of those lasers yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for QCW TFL, it has established itself as a effective and safe device for EEP which is not inferior in these terms to Tm : YAG and Ho : YAG. QCW TFL may be safer than Tm : YAG in terms of carbonizationthe quasi-continuous mode decreases the thermal damage to tissue reducing carbonization and simplifying the intraoperative navigation (16,17). Unfortunately, there is no one preclinical comparison of those lasers yet.…”
Section: Discussionmentioning
confidence: 99%
“…TFL construction substantially differs from Tm : YAG. Firstly, the YAG laser medium was replaced with thulium doped silica fiber (16,17). Thulium was chosen because the wavelength it creates is the closest to the water absorption peak (TFL -1940 nm, water -1910).…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized trial of HoLEP and TFL laser enucleation of the prostate (ThuFLEP) revealed that the deeper ablation and coagulation zones with TFL do not translate into higher rates of urinary incontinence and irritation after surgery (assessed with QUID, ICIQ-MLUTS) [17] . Despite a comparable bleeding rate in these trials, TFL, owing to its better coagulation ability, should still be promising in terms of lower bleeding rates and faster hemostasis, which was confirmed in ex vivo tests [11] .…”
mentioning
confidence: 88%
“…TFL is different in that the medium is made from woven silica fiber that is chemically doped with thulium ions. This construction means that TFL devices are much smaller then Ho:YAG and Tm:YAG and prevents extensive heating; an air cooling system is sufficient for TFL, in contrast to the water cooling systems required for Ho:YAG and Tm:YAG [11] . However, this is not the only advantage: solid-state lasers use flash lamps as the energy source for the firing, while TFL uses small diodes.…”
mentioning
confidence: 99%
See 1 more Smart Citation